Spinal cord organogenesis model reveals role of Flk1+ cells in self-organization of neural progenitor cells into complex spinal cord tissue - Baohan Pan; Hushan Ao; Su Liu; Yuming Xu; John W. McDonald; Visar Belegu (Stem Cell Research, 2018)
A platform for studying spinal cord organogenesis in vivo where embryonic stem cell (ESC)-derived neural progenitor cells (NPC) self-organize into spinal cord-like tissue after transplantation in subarachnoid space of the spinal cord has been described. We advance the applicability of this platform by imaging in vivo the formed graft through T2w magnetic resonance imaging (MRI). Furthermore, we used diffusion tensor imaging (DTI) to verify the stereotypical organization of the graft showing that it mimics the host spinal cord. Within the graft white matter (WM) we identified astrocytes that form glial limitans, myelinating oligodendrocytes, and myelinated axons with paranodes. Within the graft grey matter (GM) we identified cholinergic, glutamatergic, serotonergic and dopaminergic neurons. Furthermore, we demonstrate the presence of ESC-derived complex vasculature that includes the presence of blood brain barrier. In addition to the formation of mature spinal cord tissue, we describe factors that drive this process. Specifically, we identify Flk1+ cells as necessary for spinal cord formation, and synaptic connectivity with the host spinal cord and formation of host-graft chimeric vasculature as contributing factors. This model can be used to study spinal cord organogenesis, and as an in vivo drug discovery platform for screening potential therapeutic compounds and their toxicity. Keywords: Embryonic stem cells, Neural progenitor cells, Spinal cord organogenesis, Flk1